A STUDY ON THE INCIDENCE OF CLINICAL MASTITISIN DAIRY COWS - A. Yass, A.; A Yousif, A.; A. AL-Graibawi, M. (The Iraqi Journal of Veterinary Medicine, 1992)
Out of 720 cows milk samples examined, the incidence of clinical mastitis was found to be 33.01%. Hind quarters were more frequently affected than fore ones. The prevalence of mastitis increased with advancing age. It became highest during the sixth lactation. Bacteriological examination of milk samples revealed that Staph. aureus was the major etiological agent (46.32%), followed by Str. agalactiae (16.84%), E. coli (12.63%), Str. dysgalactiae (8.42%), C.pyogenes (8.42%) Staph. epidermidis (4.21%) Str. uberis (2.10%) and Str. pyogenes (1.05%).